Analisis Pemanfaatan Limbah Abu Kelapa Sawit Sebagai Adsorben dalam Menurunkan Logam Besi (Fe) pada Air Asam Tambang - Assegaf, Mohd Hilal; Rosyani, Rosyani; Alamsyah, Zulkifli (Universitas Batanghari Jambi, 2024)
The aim of this research is to analyze the comparative ability of boiler ash and incinerator ash in reducing Fe metal levels in Acid Mine Water, analyze the effect of mass variations and pH variations of the POFA adsorbent and analyze the adsorption ability. The flow in this research is adsorbent activation, taking Acid Mine Water samples, testing the initial conditions of Acid Mine Water samples which include pH and Fe testing and the AAT adsorption experimental stage, acid mine water sample volume 250 ml for each experiment, stirring speed 300 rpm and contact time. for 3 hours with adsorbent masses used of 2.5g, 5g and 10g, and pH variations of 5, 7 and 9, data analysis stage of adsorption capacity data. Based on research results, boiler ash is better at adsorbing Acid Mine Water, the greater the POFA adsorbent mass has the ability to reduce Fe metal because the removal percentage is greater. The best pH for adsorption treatment is pH 7, namely neutral pH, the most optimal mass of adsorbent used is 10g with a pH value of 7. The regression value on the Langmuir Isotherm is higher than the Regression value on the Freundlich Isotherm, so the Langmuir Isotherm is better for find out how much adsorbate mass can be adsorbed by the adsorbent.